PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA DINAS SOSIAL PROVINSI KOTA YOGYAKARTA BIDANG OPERASONAL - Sugeng Widodo (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to describe: (1) the influence of transformational leadership on job satisfaction; (2) the effect of compensation on job satisfaction; (3) the influence of work motivation on job satisfaction; (4) the influence of transformational leadership, compensation and work motivation together on job satisfaction This research is a quantitative research. The population in this study are employees of "Yogyakarta Province Social Service Department Operational Section". The sample of the study was 46 employees. Data collection was done by using questionnaire method. Data analysis technique used is regression technique supported by T test, path analysis test and classical assumption test with SPSS 20.00 for windows application. The result of data analysis with significance 0,05 shows that there is no positive and significant influence between transformational leadership to job satisfaction. There is no positive and significant influence between compensation on job satisfaction. There is a positive and significant influence between work motivation on job satisfaction. And There is a positive and significant influence of transformational leadership, compensation and work motivation on job satisfaction at employees at the Yogyakarta Provincial Social Office of Operational Section.